1996
DOI: 10.1111/j.1469-8137.1996.tb01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat differentiation in a narrow hybrid zone between diploid and tetraploid Anthoxanthum alpinum

Abstract: summary Populations of diploid and autotetraploid Anthoxanthum alpinum A. & D. Löve formed a narrow hybrid zone in a study area in the Swiss Prealps. Detailed vegetation analyses were performed along transects in several contact zones between the two cytotypes. The vegetation differed according to the position in the hybrid zone. When considering the hybrid zone as a whole, and for one transect that was analysed in detail, there was strong evidence for habitat segregation between the cytotypes. Vegetation tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 50 publications
4
85
2
Order By: Relevance
“…In plant polyploid complexes, such situations are commonly observed. These may involve either taxa possessing different ploidy levels (see case studies of ; Van Dijk, Hartog & Van Delden (1992), Felber-Girard, Felber & Buttler (1996) ; Petit et al (1997)), or secondary contact between entities that have the same ploidy level, but which have been subject to long-term genetic differentiation in separate areas or are derived from distinct parental taxa of the same species. In areas where taxa of the same ploidy level of a single species occur sympatrically, habitat differentiation and\or reproductive isolation (say, differences in flowering time) may occur but generally, hybridization is possible, and might include subsequent genetic introgression between the taxa (Rieseberg & Wendel, 1993).…”
Section: mentioning
confidence: 99%
“…In plant polyploid complexes, such situations are commonly observed. These may involve either taxa possessing different ploidy levels (see case studies of ; Van Dijk, Hartog & Van Delden (1992), Felber-Girard, Felber & Buttler (1996) ; Petit et al (1997)), or secondary contact between entities that have the same ploidy level, but which have been subject to long-term genetic differentiation in separate areas or are derived from distinct parental taxa of the same species. In areas where taxa of the same ploidy level of a single species occur sympatrically, habitat differentiation and\or reproductive isolation (say, differences in flowering time) may occur but generally, hybridization is possible, and might include subsequent genetic introgression between the taxa (Rieseberg & Wendel, 1993).…”
Section: mentioning
confidence: 99%
“…Adaptive strategies are needed for establishment and persistence of new polyploids. Such strategies include apomixis (Hedrén et al 2000), self-pollination (Levin 1975), pollinator shift (Segraves and Thompson 1999) and habitat differentiation (Felber-Girard et al 1996). However, even though the literature on polyploidy is comprehensive there are relatively few studies that focus on the ecological aspects of polyploidization (Soltis et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, when different cytotypes co-exist sympatrically, they often show fine-scale niche differentiation, shift in flowering time, or increased selfing (e.g. Lumaret & Hanotte, 1987 ;Lumaret & Barrientos, 1990 ;Felber-Girard et al, 1996 ;, but no such phenomenon was observed in knapweeds. The significant reduction of seed set and germination rate obtained for intercytotype controlled crosses (Gardou, 1972 ;O.…”
Section: Occurrence Of Mixed Populationsmentioning
confidence: 99%
“…Within contact zones, cytotypes usually show spatial segregation (e.g. Van Dijk et al, 1992 ;Felber-Girard et al, 1996 ;Burton & Husband, 1999) as a result of niche differentiation and\or of a ' minority cytotype exclusion ' effect (Levin, 1975) caused by unsuccessful intercytotype crosses. The relative significance of these phenomena is, however, controversial (Van Dijk & Bakx-Schotman, 1997 ;Petit et al, 1999).…”
Section: mentioning
confidence: 99%